Mixed-methods feasibility study of blood pressure self-screening for hypertension detection. Issue 5 (29th May 2019) - Tompson, Alice; Fleming, Susannah; Lee, Mei-Man; Monahan, Mark; Jowett, Sue; McCartney, David; Greenfield, Sheila; Heneghan, Carl; Ward, Alison; Hobbs, Richard; McManus, Richard J
Abstract : Objective: To assess the feasibility of using a blood pressure (BP) self-measurement kiosk—a solid-cuff sphygmomanometer combined with technology to integrate the BP readings into patient electronic medical records— to improve hypertension detection. Design: A concurrent mixed-methods feasibility study incorporating observational and qualitative interview components. Setting: Two English general practitioner (GP) surgeries. Participants: Adult patients registered at participating surgeries. Staff working at these sites. Interventions: BP self-measurement kiosks were placed in the waiting rooms for a 12-month period between 2015 and 2016 and compared with a 12-month control period prior to installation. Outcome measures: (1) The number of patients using the kiosk and agreeing to transfer of their data into their electronic medical records; (2) the cost of using a kiosk compared with GP/practice nurse BP screening; (3) qualitative themes regarding use of the equipment. Results: Out of 15 624 eligible patients, only 186 (1.2%, 95% CI 1.0% to 1.4%) successfully used the kiosk to directly transfer a BP reading into their medical record. For a considerable portion of the intervention period, no readings were transferred, possibly indicating technical problems with the transfer link. A comparison of costs suggests that at least 52.6% of eligible patients would need to self-screen in order to bring costs below that of screening by GPs and practice nurses. Qualitative interviews confirmed that both patients and staff experienced technical difficulties, and used alternative methods to enter BP results into the medical record. Conclusions: While interviewees were generally positive about checking BP in the waiting room, the electronic transfer system as tested was neither robust, effective nor likely to be a cost-effective approach, thus may not be appropriate for a primary care environment. Since most of the cost of a kiosk system lies in the transfer mechanism, a solid-cuff sphygmomanometer and manual entry of results may be a suitable alternative.